Spectrophotometric Determination of Sulphadiazine Using 2,4 –dinitrophenylhydrazine as Coupling Reagent - Najlaa Abd AL Salam Ahmed; Ali Ibraheem Khaleel (Tikrit Journal of Pure Science)
A rapid, sensitive and selective spectrophotometric method was developed for determination of sulphadiazine   in aqueous solution. The method is based on the oxidative coupling reaction with 2,4-dinitrophenylhydrazine (2,4-DNPH) in a basic medium in the presence of potassium periodate to produce an intense orange colour product, soluble in water, stable and absorbs at 486 nm. The linearity of Beer's law is in the range 3-15μg/ml of sulphadiazine. The molar absorptivity, Sandellʼs sensitivity index, and detection limit were 2.23x104liter.mol-1. cm-1, 0.0222 μg.cm-2 and 0.0307μg/ml respectively. The RSD value was 0.506 – 0.116 % depending on the concentration value. This method is applied successfully to the determination of sulphadiazine veterinary injection liquid solution (VAPCOTRIM) with average recovery of not less than 99.5%.